Association of epigenetic aging with plasma biomarkers of amyloid, tau, neurodegeneration, and neuroinflammation in Hispanic/Latino adults - Myriam Fornage; Wassim Tarraf; Martha L. Daviglus; Charles DeCarli; Kevin A. Gonzalez; Carmen R. Isasi; Sayaka Kuwayama; Melissa Lamar; Bonnie E. Levin; Humberto Parada; Alberto R. Ramos; Tatjana Rundek; et al. (Clinical Epigenetics)
Abstract Background Blood-based biomarkers hold significant promise for the early detection and diagnosis of Alzheimer’s disease (AD) and other dementias. Age-related changes in blood levels of AD biomarkers are well-documented but poorly understood. Epigenetic clocks are mathematical models based on DNA methylation patterns that reflect various aspects of the multidimensional aging process. We investigated the associations of epigenetic aging with five blood-based AD biomarkers in 2656 Hispanic/Latino adults (mean age 62.5 years; 65% females) from the Hispanic Community Health Study/Study of Latinos. We used multivariable linear regression models to estimate the associations of acceleration in each of five epigenetic clocks with each biomarker in the total sample and in sex-specific strata, controlling for chronological age, sex (except in sex-stratified analyses), Hispanic/Latino background, recruitment site, risk factors, and comorbid medical conditions. Results There were varying strengths of association between acceleration of the clocks and the plasma biomarkers. There were significant associations of acceleration in all epigenetic clocks with higher plasma levels of neurofilament light chain (NfL) (Beta = 0.0045 to 0.0193; P = 0.022 to 4.9 × 10–15). There were significant associations of acceleration in all epigenetic clocks except DunedinPACE with higher plasma levels of amyloid beta (Aβ)40 (Beta = 0.0033 to 0.0049; P = 0.024 to 1.7 × 10–5). PC-PhenoAge acceleration was associated with all circulating biomarkers but its associations with Aβ42, Aβ42/40 ratio, and phosphorylated Tau 181 (p-Tau181) showed heterogeneity by sex. Specifically, PC-PhenoAge acceleration was associated with higher Aβ42 and p-Tau181 levels in males (Beta = 0.0066, P = 0.002 and Beta = 0.0158, P = 2 × 10–4, respectively) but not females, while it was associated with lower Aβ42/40 ratio in females (Beta = − 0.0032, P = 0.012) but not males. Conclusions Epigenetic age acceleration is associated with circulating biomarkers of AD in Hispanic/Latino adults. The second‐generation clock PC-PhenoAge showed strong and consistent associations across all biomarkers, and thus may reflect biological processes most relevant to age-related changes in AD biomarkers. Considering sex differences in the relationship between biological aging and circulating AD biomarkers is paramount.